2023
DOI: 10.1111/psyp.14444
|View full text |Cite
|
Sign up to set email alerts
|

Feedback negativity and feedback‐related P3 in individuals at risk for depression: Comparing surface potentials and current source densities

Yifan Gao,
Lidia Y. X. Panier,
Marc J. Gameroff
et al.

Abstract: Blunted responses to reward feedback have been linked to major depressive disorder (MDD) and depression risk. Using a monetary incentive delay task (win, loss, break‐even), we investigated the impact of family risk for depression and lifetime history of MDD and anxiety disorder with 72‐channel electroencephalograms (EEG) recorded from 29 high‐risk and 32 low‐risk individuals (15–58 years, 30 male). Linked‐mastoid surface potentials (ERPs) and their corresponding reference‐free current source densities (CSDs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 162 publications
1
1
0
Order By: Relevance
“…Hence, the most likely explanation for the differential FRN pattern appears to be a processing bias of the SCD group toward negative performance feedback. Given the fact that groups with a tendency to preferentially process negative information like patients with depression and anxiety have been reported to show enhanced FRN amplitudes to negative feedback ( Santesso et al, 2012 ; Keren et al, 2018 ; Tobias and Ito, 2021 ; but see Gao et al, 2024 for a different result), this is in line with the fact that the SCD group showed stronger symptoms of depression and anxiety than the No-SCD group ( Table 1 ). Some indirect evidence for a role of depressive symptoms in the present result pattern comes from the fact that the group × valence interaction missed the significance level when statistically controlling for depressive symptoms.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Hence, the most likely explanation for the differential FRN pattern appears to be a processing bias of the SCD group toward negative performance feedback. Given the fact that groups with a tendency to preferentially process negative information like patients with depression and anxiety have been reported to show enhanced FRN amplitudes to negative feedback ( Santesso et al, 2012 ; Keren et al, 2018 ; Tobias and Ito, 2021 ; but see Gao et al, 2024 for a different result), this is in line with the fact that the SCD group showed stronger symptoms of depression and anxiety than the No-SCD group ( Table 1 ). Some indirect evidence for a role of depressive symptoms in the present result pattern comes from the fact that the group × valence interaction missed the significance level when statistically controlling for depressive symptoms.…”
Section: Discussionsupporting
confidence: 59%
“…However, prior results are not entirely consistent. For example, Gao et al (2024) found no association between affective symptoms and FRN amplitude. Nevertheless, it appears that a processing bias toward negative information may go hand in hand with an enhanced FRN to negative feedback.…”
Section: Introductionmentioning
confidence: 94%